Pengaruh Pengungkapan Emisi Karbon, Dewan Komisaris Independen, dan Modal Intelektual terhadap Kinerja Keuangan - Roro Ajeng Ristanti; Adi Wiratno; Izzati Amperaningrum (Jurnal Riset Akuntansi Soedirman, 2025)
This study, entitled "The Effect of Carbon Emission Disclosure, an Independent Board of Commissioners, and Intellectual Capital on Financial Performance," aims to examine and analyze the influence of carbon emission disclosure, an independent board of commissioners, and intellectual capital on financial performance. Signaling and agency theory serve as the foundation for this research. A causal quantitative approach using secondary data from financial reports and sustainability reports was employed. The population of this study was energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. A purposive sampling technique was used to select the sample, resulting in 31 companies. The data analysis techniques employed included descriptive statistical analysis, panel data regression models, panel data regression model selection tests, classical assumption tests, panel data regression analysis, model feasibility tests, and hypothesis testing. This study found that: (1) carbon emission disclosure has no effect on financial performance; (2) an independent board of commissioners has no effect on financial performance; and (3) intellectual capital has an effect on financial performance. The implications of this research are that companies are expected to consistently disclose and improve the quality of their carbon emissions disclosures. Companies should ensure that independent boards of commissioners effectively monitor and manage their operations, and they are advised to improve their intellectual capital management. Before investing, investors are advised to consider factors such as carbon emissions disclosure, the presence of an independent board of commissioners, and the company's intellectual capital.